THE ORIGINALITY OF THE HANDMAID'S TALE & THE CHILDREN OF MEN: RELIGION, JUSTICE, AND FEMINISM IN DYSTOPIAN FICTION. - Bacci, Francesco (Metacritic Journal for Comparative Studies & Theory, 2017)
The aim of this paper is to analyze the theoretical challenges and the approach through which The Handmaid's Tale and The Children of Men describe a world which is destroying itself in a society where human rights do not matter. The main objective is to discuss the role of women in these narrative universes. A space will also be created to consider how the female condition is perceived as a threat to a totalitarian society. In doing so, we will undertake this research with a multidisciplinary approach which takes into consideration the novels and the on- screen adaptations of these two stories. The end of the world is described and portrayed with a peculiar research of details that can convey this general idea of hopelessness. This paper wants to explore and create a detailed socio-cultural perspective on these two novels and movies with the support of a series of academic references to gender and dystopian studies.